Legal Gap In The Determination of Moderate Wound By Forensic Doctors On Visum Et Repertum In Criminal Case - Wahyu Putra Pratama, S.Kep (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
The present research is about “Legal Gap in Determination of Moderate Wounds by forensic pathologists on Visum Et Repertum in Criminal Court”. There is a problem that legal concept of moderate wound on visum et repertum and legal gap for determining the state of moderate wounds by forensic pathologists at Visum et Repertum. This is a normative research with conceptual approach, statute approach, and case approach. Legal experts acknowledge moderate wound, which is a kind of wound or injury in between a minor and severe conditions. A legal gap created by the absence of moderate wound in law which is a familiar term criminal court. Regarding forensic pathologists competensies, they determine moderate injuries victims whose have economic impaired without physical disturbance.